2001
DOI: 10.1006/gcen.2001.7695
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sex Steroids on the Sexual Size Dimorphism in the Red-Spotted Garter Snake, Thamnophis sirtalis concinnus

Abstract: The red-spotted garter snake exhibits adult size dimorphism in which females are the larger sex. To understand which hormones may influence differential growth in this species, growth curves and hormone profiles of estradiol-17␤ (E 2 ) and testosterone (T) were constructed in male and female neonates. Growth was manipulated via implantation of exogenous hormones and hormone antagonists. Female neonates are heavier or longer beginning at either 20 or 24 weeks of age, respectively. Although low circulating level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…elongation) by T in any squamate reptile. Although prenatal exposure to T stimulates postnatal mass gain in the lizard Lacerta vivipara (Uller and Olsson, 2003), every other study involving lizards and snakes has found either no effect or an inhibitory effect of T on skeletal growth or mass gain (Abell, 1998a;Cox et al, 2005;Crews et al, 1985;Hews et al, 1994;Hews and Moore, 1995;Klukowski et al, 1998;Lerner and Mason, 2001;Moore, 1989, 1991;Salvador and Veiga, 2000). While these studies collectively suggest that growth inhibition by T may be prevalent in this group, several caveats beg mention.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…elongation) by T in any squamate reptile. Although prenatal exposure to T stimulates postnatal mass gain in the lizard Lacerta vivipara (Uller and Olsson, 2003), every other study involving lizards and snakes has found either no effect or an inhibitory effect of T on skeletal growth or mass gain (Abell, 1998a;Cox et al, 2005;Crews et al, 1985;Hews et al, 1994;Hews and Moore, 1995;Klukowski et al, 1998;Lerner and Mason, 2001;Moore, 1989, 1991;Salvador and Veiga, 2000). While these studies collectively suggest that growth inhibition by T may be prevalent in this group, several caveats beg mention.…”
Section: Discussionmentioning
confidence: 96%
“…While these studies collectively suggest that growth inhibition by T may be prevalent in this group, several caveats beg mention. First, several of the above studies reported severe mass loss and/or reduced survival among Timplanted animals (Abell, 1998a;Hews et al, 1994;Hews and Moore, 1995;Lerner and Mason, 2001), prompting some authors to acknowledge concerns over pharmacological T levels (Hews et al, 1994, pp. 110-112;Hews and Moore, 1995, p. 99;Lerner and Mason, 2001, p.223).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study on Psammodromus algirus reported that individuals treated with testosterone tended to grow less than control individuals, but found no significant effect, probably due to the small sample size (Salvador and Veiga, 2000). In the snake Thamnophis sirtalis, testosterone also did not have significant effects on structural growth (SVL) in a short-term study with adult males (Crews et al, 1985), while addition of testosterone proved to be lethal in neonatal males of the same species (Lerner and Mason, 2001). Overall, it seems that testosterone supplementation in gonadally intact males can lead to detrimentally high, supra-physiological doses.…”
Section: Discussionmentioning
confidence: 97%
“…Effects on growth of female gonadal hormones have rarely been tested in squamate reptiles (but see Lerner and Mason, 2001) [for evidence in other vertebrates, see Malison et al (Malison et al, 1988) or Govoni et al (Govoni et al, 2008)], which precludes evaluating whether estrogens or progestins may affect female growth in the opposite direction in female-versus male-larger lizard species [see Cutler (Cutler, 1997) for support for the role of low levels of estrogens in regulation of growth in humans]. Testing this hypothesis will require further experimental work focused specifically on hormonal manipulations in females of male-larger and female-larger species.…”
Section: Discussionmentioning
confidence: 99%